PEMANFAATAN KOMIK BENCANA ALAM SEBAGAI MEDIA EDUKASI KESIAPSIAGAAN BENCANA SISWA SEKOLAH DASAR - Rijal Sidik Almudakir; Pidi Mohamad Setiadi; Riefki Fiestawa (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Understanding environmental conditions that have the potential to cause disasters is an essential competency that should be instilled in elementary school students as part of efforts to develop disaster preparedness from an early age. Disasters can occur unexpectedly and have significant impacts on various aspects of human life; therefore, educational initiatives are needed to enhance students’ knowledge and readiness in dealing with emergency situations. This study aims to analyze the utilization of natural disaster comics as a facilitator of disaster preparedness understanding among elementary school students through a literature review. The method employed in this study was a literature review by examining various scientific articles, books, and relevant documents related to instructional media, disaster education, disaster preparedness, and the use of comics in learning. Data were collected through a search of relevant scientific sources, particularly through Google Scholar, and were subsequently analyzed using content analysis techniques. The findings indicate that natural disaster comics have significant potential as an effective medium for improving students’ understanding of disaster-related concepts and preparedness measures. The presentation of information through a combination of text and engaging visual illustrations can increase students’ learning interest, engagement, and retention of the material. Furthermore, disaster comics help students understand appropriate actions before, during, and after a disaster through contextual and easily comprehensible scenarios. Therefore, natural disaster comics can serve as an innovative alternative in disaster education, as they facilitate students’ understanding of disaster preparedness while fostering attitudes of awareness, responsiveness, and readiness toward potential disaster risks in their surrounding environment.